2017
DOI: 10.1111/1365-2745.12761
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic responses to conspecific and congeneric competition in co‐occurring Trifolium

Abstract: 1. Species coexistence requires differential response to inter-and intraspecific competition, typically conceptualized as niche differentiation. Coexistence of close relatives therefore poses an interesting scenario with regards to niche differentiation since these species generally have many traits in common due to shared ancestry. Native Californian Trifolium assemblages are locally diverse and represent a unique system for understanding competitive interactions among close relatives.2. We conducted two simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 102 publications
0
37
0
Order By: Relevance
“…Ethylene‐related genes were up‐regulated in Trifolium fucatum when competing with its congeneric T . macraei (Bowsher et al ., ). In addition, two candidates underlying two other QTLs of response to inter‐genotypic competition in A .…”
Section: The Genetics Of Natural Variation Of Plant–plant Interactionsmentioning
confidence: 97%
See 4 more Smart Citations
“…Ethylene‐related genes were up‐regulated in Trifolium fucatum when competing with its congeneric T . macraei (Bowsher et al ., ). In addition, two candidates underlying two other QTLs of response to inter‐genotypic competition in A .…”
Section: The Genetics Of Natural Variation Of Plant–plant Interactionsmentioning
confidence: 97%
“…thaliana , two studies reported an up‐regulation of defense‐related genes (Biedrzycki et al ., ; Masclaux et al ., ), while a third study reported the opposite pattern (Geisler et al ., ). Up‐regulation and down‐regulation of defense‐related genes were even reported within the same studies (Horvath et al ., ; Bowsher et al ., ). The growth‐defense balance theory predicts that light perception by photoreceptors activates SAS and reduces the expression of defenses against microbial pathogens and insects, by a simultaneous down‐regulation of jasmonate and salicylic acid signaling (Ballaré, ; Ballaré and Pierik, ).…”
Section: The Genetics Of Natural Variation Of Plant–plant Interactionsmentioning
confidence: 97%
See 3 more Smart Citations